2021
DOI: 10.1155/2021/5523490
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Serum Uric Acid in Gout with Cerebral Infarction

Abstract: Background. Although the relationship between gout and cardiovascular has been well demonstrated, there is little information about the difference between gout with cerebrovascular disease and cardiovascular disease. In this study, the differences between gout with cerebral infarction (gout+CI) and gout with coronary heart disease (gout+CHD) and related factors that affect serum uric acid (sUA) levels in gout+CI were investigated by a cross-sectional study. Method. The patients from Jiangxi Provincial People’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…As the comparation of demographic data in Table 1, the difference of age among three groups was significant, moreover, we did a partial correlation analysis, which controls the influence of the diagnosis and sex, the result showed that the association between age and UA was significantly negative. The previous study also showed that age was negatively correlated with the UA level 32 . To eliminate the influence of confounding factors, we set the age as covariates when we conducted the comparation.…”
Section: Discussionmentioning
confidence: 79%
“…As the comparation of demographic data in Table 1, the difference of age among three groups was significant, moreover, we did a partial correlation analysis, which controls the influence of the diagnosis and sex, the result showed that the association between age and UA was significantly negative. The previous study also showed that age was negatively correlated with the UA level 32 . To eliminate the influence of confounding factors, we set the age as covariates when we conducted the comparation.…”
Section: Discussionmentioning
confidence: 79%